Learning mathematics outcomes using Android for blind students based on Newman's theory - Agustina, Rina; Farida, Nurul; Irfan, Muhammad (Intelektual Pustaka Media Utama, 2024)
Blind students exclusively use braille materials for teaching math. Teaching tools that assist blind students' motor and hearing nerves are essential for learning. This study was to describe learning mathematics outcomes for blind students after using teaching material for Android devices based on Newman's theory. This research was a case study of blind students. Blind junior high school students from special schools for visual impairment—extraordinary schools in Bandar Lampung, extraordinary schools in Cimahi, and Madrasah Tsanawiyah with special education in Yogyakarta—contributed to the study's subjects. The study employed questionnaires and test questions as research instruments for both teachers and students. The results of this study demonstrate that learning mathematics outcame blind students' after using teaching material with Android apps based on Newman's theory, specifically: i) reading errors: students can understand the information in the questions; ii) comprehension errors: students do not write down things that are known and asked; and iii) transformation errors: students write down the mathematical model (formula) used; iv) skill errors: students can do calculations correctly; and v) coding errors: students do not write conclusions. The average score of the blind students’ results using braille was higher than that of the Android application.